The water supply project = (The World Bank in Vietnam (WB), 2003)
The aims of the Water Supply Project in Hanoi, Haiphong, Halong City/Cam Pha in Quang Ninh, and Danang are to: (i) improve the quality of water supply services in the four cities through renovation of existing facilities in order to satisfy demand up to 2000 of about 2.5 million people in the cities; (ii) ensure sustainability of the physical investments by developing the institutional capabilities of water supply agencies, facilitating their commercialization, and upgrading their staff skills through training; and (iii) assist in preparation of a future investment program to satisfy water demand after 2000. The project will include the following components: 1) renewal and upgrading of water supply facilities in the urban districts of Hanoi, Haiphong and Danang, and Halong/Cam Pha in Quang Ninh province; 2) institutional measures to ensure sustainability of the physical investments; 3) support activities consisting of various studies, advisory services, supervision of construction and training; and 4) resettling and rehabilitating of population affected by the project.